Dynamics in the contaminant micro flora of choro, Aulacomya ater processed and raw ceviche. 2 - Qualitative analysis. - Coha, Juana (1974)
In 64 samples (1,152 specimens) from the mollusk Aulacomya ater "choro" gotten from Lima and Callao markets, It was isolated three main bacterial groups: Enteric, Streptococci and Micrococci. The high average of E. coli; from "choro" uncooked (part a) and "cebiche” (part c), show us, human fecal contamination as in the Quantitative Analysis. On the other hand occurs that the group Enterococci is only in "choro" uncooked. It is important to remark the relationship between E. coli, Streptococcus Lancenfield group D, in each part of fixing "cebiche", besides the latter microorganisms occurs with high frequency in "cebiche" (part a) as a result of using condiments and manipulation.